2015
DOI: 10.4081/mrm.2015.275
|View full text |Cite
|
Sign up to set email alerts
|

Tailored therapy for severe asthma

Abstract: Patients with severe asthma or COPD have often a suboptimal symptom control due to inadequate treatment. A better understanding of pathogenetic mechanisms, phenotypes, endotypes and the new technologies available in the fields of molecular biology and immunogenetics have made it possible to synthesize specific monoclonal antibodies virtually able to interact with any target antigen, or to open a way for new therapeutic target options. At the moment, the only biologic drug available in clinical practice is omal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Phenotypes, the outward manifestation of an individual's underlying genetics, have been widely accepted as a way to characterize patients with asthma (76)(77)(78)(79)(80)(81) and include clinical, physiologic, inflammatory, and molecular features. Stratification of asthma subtypes by phenotype and endotype (i.e., specific biologic mechanisms) represents the cutting edge for advancing asthma treatment.…”
Section: Current Understanding Of Phenotypes Of Aiementioning
confidence: 99%
“…Phenotypes, the outward manifestation of an individual's underlying genetics, have been widely accepted as a way to characterize patients with asthma (76)(77)(78)(79)(80)(81) and include clinical, physiologic, inflammatory, and molecular features. Stratification of asthma subtypes by phenotype and endotype (i.e., specific biologic mechanisms) represents the cutting edge for advancing asthma treatment.…”
Section: Current Understanding Of Phenotypes Of Aiementioning
confidence: 99%
“…Over the last 40 years, there has been a marked increase in the development of targeted treatments for asthma-anti-leukotrienes, anti-IgE, anti-interleukins, and anti-TNF-α [115]. Obviously, as more of the biological basis of asthma is uncovered, more effective targeted asthma treatments might be developed.…”
Section: Targeted Therapiesmentioning
confidence: 99%
“…Omalizumab (Xolair®) is a humanized monoclonal antibody that binds to free, circulating IgE. This prevents IgE binding to high (FcεRI) and low affinity (FcεRII) IgE receptors on mast cells and basophils, thereby inhibiting the degranulation and release of inflammatory mediators (8). A systematic review by Rodrigo et al (9) found that omalizumab therapy was able to reduce the rate of asthma exacerbations by up to 50% and significantly improve quality of life scores of allergic asthmatics (9).…”
Section: Anti-ige Therapy -Omalizumab and Beyondmentioning
confidence: 99%
“…Another alternative, quilizumab, which targets M1-prime (a protein specific to membrane bound IgE+ B cells), has been shown to reduce the production of IgE after allergen inhalation challenge (11). Despite the therapeutic potential of anti-IgE, major drawbacks of antibody therapies are their cost and that they must be taken regularly for long-term treatment as their effects are known to wane following the termination of treatment (8). Additionally, anti-IgE therapies are prescribed to a small proportion of patients with moderate-severe allergic asthma.…”
Section: Anti-ige Therapy -Omalizumab and Beyondmentioning
confidence: 99%